Supplemental Zinc Sulfate Affects Growth Performance of Finishing Heifers - C. L. Van Bibber-Krueger; J. S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2016)
Zinc is an essential mineral required for normal function of more than 300 enzymes in microorganisms, plants, and animals. Zinc-requiring enzymes participate in metabolism of nucleic acids, proteins, and carbohydrates, all of which are essential for growth of cattle. In addition, zinc is necessary for normal development and function of the immune system. The requirement for zinc in finishing cattle diets has been established at 30 ppm (NRC, Nutrient Requirements of Beef Cattle, 2000), though concentrations recommended by consulting nutritionists and feed manufacturers span a far broader range. The purpose of this study was to evaluate the effects of feeding different levels of zinc on feedlot performance and carcass traits of finishing heifers.
Keywords: zinc; feedlot; carcass